Up jumps the devil eaudiobook Deborah knott mysteries series, book 4. - Maron, Margaret (Judge Deborah Knott, 1997)
Best-selling author Margaret Maron's colorful Deborah Knott mysteries crackle with sassy Southern dialogue and rural wisdom. In Up Jumps the Devil, fast-moving progress is threatening to forever destroy the leisurely, heart-warming pace of Colleton County, North Carolina. District court judge Deborah Knott sees trouble brewing when plans for a new interstate highway start pushing up property values. As her own relatives battle lifelong neighbors over selling farmland or holding out, Deborah finds herself calming the combatants with down-home wit-and sometimes, judicial decisions. But when the squabbles escalate to murder, Deborah is forced to search for the killer uncomfortably close to home. Margaret Maron skillfully draws on her North Carolina roots to pen her well-crafted, suspenseful mysteries. Her creative talents have earned her the coveted Edgar, Agatha, Macavity, and Anthony Awards. Salt-of-the-earth characters, vivid with lilting, down-home humor and unwavering opinions, step from the pages when narrator C.J. Critt breathes life into them.